Low-spin [MII(L)2] and [MIII(L)2]+ (M = Fe and Co) complexes of tridentate azo-containing pyridine/pyrazine amide ligands: structures, properties and redox potential correlations. Issue 34 (14th August 2017) - Sengupta, Arunava; Rajput, Amit; Barman, Suman K.; Mukherjee, Rabindranath
Abstract : Comparative molecular (X-ray) and electronic (DFT, TD-DFT) structural studies have been done; the E 1/2 values (M III /M II couple) for Fe, Co and Ni complexes linearly correlate with other low-spin complexes. Abstract : Using deprotonated forms of tridentate azo-containing pyridine-2-/pyrazine-2-carboxamide 2-[ N -(2-phenylazo)carbamoyl]-pyridine/pyrazine, seven bis-ligand complexes of Fe II /Co II and Fe III /Co III have been synthesized. Molecular structures of six of them reveal that these six-coordinate complexes utilize all available donor sites of the ligands and assume M II/III N2 (pyridine/pyrazine)N′2 (amide)N′′2 (azo) coordination. Complexes of Fe II and Co III are diamagnetic and those of Fe III and Co II are paramagnetic ( S = 1/2; room-temperature magnetic data and EPR spectra). Cyclic voltammetry experiments in CH2 Cl2 reveal facile metal-centred Fe III /Fe II and Co III /Co II redox responses, and all complexes display quasireversible-to-irreversible ligand(azo)-centred redox processes. The E 1/2 values of M III /M II redox processes for Fe, Co and Ni (reported earlier) complexes of the pyridine amide ligand linearly correlate with those for six-coordinate [M III (bpy)3 ] 3+ /[M II (bpy)3 ] 2+, [M III (terpy)2 ] 3+ /[M II (terpy)2 ] 2+, [M III (L)] + /[M II (L)] 0 or [M III (L′)2 ] + /[M II (L′)2 ] 0 (bpy = 2, 2′-bipyridine, terpy = 2, 2′:6′, 2′′-terpyridine, hexadentate L(2−) = 1, 4-bis[ o -(pyridine-2-carboxamidophenyl)]-1, 4-dithiobutane and tridentate L′(−) = 2-[2-(arylimino)phenylazo]-pyridine) couples. Density functional theory (DFT) at the B3LYP level and time-dependent (TD)-DFT calculations rationalize the electronic structure of the present complexes and throw light on the origin of observed electronic transitions.